PENGARUH MANAJEMEN RANTAI PASOK BERBASIS ERP DALAM MENINGKATKAN KINERJA PT. FURNITUR BATAM BINA PERKASA - Cuandra, Fendy; Maytanius, Jerry; Leonardo; Sembiring, Diamend Tino; Lim, Ricky (Transpublika Publisher, 2022)
Business development in the era of the 21st century has grown very rapidly and has undergone a continuous metamorphosis. Every business actor in every business category is required to be sensitive to any changes that occur and place an orientation to customer satisfaction as the main goal. Supply Chain Management is a mechanism that connects all parties concerned and the activities involved in converting raw materials into finished goods. The importance of the role of all parties from suppliers, manufacturers, distributors, retailers to customers in creating cheap, quality and fast products is what gave birth to a new concept, namely supply chain management.